2011
DOI: 10.1021/mp200329f
|View full text |Cite
|
Sign up to set email alerts
|

Histone Deacetylase Inhibitors: Emerging Mechanisms of Resistance

Abstract: The histone deacetylase inhibitors (HDIs) have shown promise in the treatment of a number of hematologic malignancies, leading to the approval of vorinostat and romidepsin for the treatment of cutaneous T-cell lymphoma and romidepsin for the treatment of peripheral T-cell lymphoma by the U. S. Food and Drug Administration. Despite these promising results, clinical trials with the HDIs in solid tumors have not met with success. Examining mechanisms of resistance to HDIs may lead to strategies that increase thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
101
1
15

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(118 citation statements)
references
References 123 publications
(245 reference statements)
1
101
1
15
Order By: Relevance
“…9,10 Varinostat and romidepsin are the FDA approved HDIs approved for the treatment of cutaneous T cell lymphoma and currently many more HDIs are in clinical trials. 11, 12 Many of these HDIs are reported to induce their anticancer effect by modulating both the acetylation of histones via their primary effects on HDACs, but many of them have also been found to modulate non-histone proteins, including tubulin. 13 Triazole derivatives have been proved to possess various pharmacological properties including antiproliferative, antiretroviral, antimicrobial, anticonvulsant and transforming growth factor β1 type 1 receptor inhibition.…”
Section: Introductionmentioning
confidence: 99%
“…9,10 Varinostat and romidepsin are the FDA approved HDIs approved for the treatment of cutaneous T cell lymphoma and currently many more HDIs are in clinical trials. 11, 12 Many of these HDIs are reported to induce their anticancer effect by modulating both the acetylation of histones via their primary effects on HDACs, but many of them have also been found to modulate non-histone proteins, including tubulin. 13 Triazole derivatives have been proved to possess various pharmacological properties including antiproliferative, antiretroviral, antimicrobial, anticonvulsant and transforming growth factor β1 type 1 receptor inhibition.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14] We previously showed that HDAC inhibitor-induced autophagy significantly blunts its anticancer activity. Accordingly, genetic or pharmacological disruption of autophagy synergistically modulated the pro-apoptotic and cytostatic effects of VOR in models of imatinib-resistant chronic myeloid leukemia and colon cancer.…”
mentioning
confidence: 99%
“…The mechanisms of HDACi resistance include the upregulation of P-glycoprotein, other ATP-binding cassette transporters, cell cycle proteins and signaling proteins, alterations to HDAC protein level, increases in thioredoxin level, nuclear factor-κB activation and anti-apoptotic/prosurvival mechanisms (26). The molecular mechanism for acquired resistance varies in different HDACi-resistant cells.…”
Section: Discussionmentioning
confidence: 99%